2021
DOI: 10.1021/acs.chemmater.1c00970
|View full text |Cite
|
Sign up to set email alerts
|

Cleanly Removable Surfactant for Carbon Nanotubes

Abstract: Surfactants, molecular surface-active agents, are widely used to stabilize single-walled carbon nanotubes (SWCNTs) and many other nanomaterials in water to facilitate solution processing and device integration. However, it is notoriously difficult to cleanly remove surfactants when they are no longer needed. Even high-temperature thermal annealing leaves residues that can degrade the otherwise remarkable electrical and optical properties of SWCNTs. Moreover, thermal annealing damages smaller-diameter nanotubes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…To compensate for this, Zhang et al reported in a recent study that the use of ammonium deoxycholate as a surfactant enabled clean removal from SWNT through heat treatment. In contrast to DOC, about 20% remained; even at high temperatures above 500 °C, ADC was removed to 5% or less at 400 °C or higher [ 117 ]. Nevertheless, there is still an issue that high temperatures can cause damage to SWNTs, which is the same for acid treatment.…”
Section: Allyl Dextran-based Gelsmentioning
confidence: 99%
“…To compensate for this, Zhang et al reported in a recent study that the use of ammonium deoxycholate as a surfactant enabled clean removal from SWNT through heat treatment. In contrast to DOC, about 20% remained; even at high temperatures above 500 °C, ADC was removed to 5% or less at 400 °C or higher [ 117 ]. Nevertheless, there is still an issue that high temperatures can cause damage to SWNTs, which is the same for acid treatment.…”
Section: Allyl Dextran-based Gelsmentioning
confidence: 99%
“…[441] Similar problem is also unavoidable for surfactants and other dispersant molecules, as demonstrated by thermogravimetric analysis. [436,[442][443][444][445] Therefore, the complete removal of dispersant molecules still remains a challenge.…”
Section: Removal Of Dispersant Moleculesmentioning
confidence: 99%
“…Carbon is an amazing element that has many different stable forms including three‐dimensional diamond, 2D graphene, 1D nanotubes, and 0D fullerene. Research on carbon materials has attracted much attention in the fields of science and industrial technology since the discoveries of fullerene in 1985, [ 1 ] nanotubes in 1991, [ 2 ] and graphene in 2004. [ 3 ] Single‐wall carbon nanotubes (SWCNTs) are some of the most studied carbon materials and were produced for the first time by Iijima, Bethume et al.…”
Section: Introductionmentioning
confidence: 99%
“…For non-covalent chemical modifications, the choice of dispersing agents is crucial to the effective individualization and efficient sorting of metallic or semiconducting SWNTs. Typical dispersing agents are limited to classic surfactants [22][23][24], ionic liquids [25], and biological substances [12,26,27] applicable in water media as well as varying polymers [28][29][30] applicable in water or non-water media. In the case of polymers, both the water-soluble nonaromatic species [31][32][33] and the non-water-soluble π-conjugated ones are selective for sc-SWNTs [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%